Money Neutrality: Rethinking the Myth - Issaoui, Fakhri; Boufateh, Talel; Guesmi, Mourad (Panoeconomicus, 2015)
Considered as an axiomatic basis of classical, neoclassical, and monetarist theories, the long-run money neutrality assumption does not always seem to be verified. Indeed, in our view, the money, in the sense of M2, can constitute a long-run channel of growth transmission. Thus, this paper examines the long-term relationship among money supply (M2), income (GDP), and prices (CPI). The subprime crisis in 2007 has shown that the demand for money does not only meet motives of transaction, precaution, and speculation but also of fictional or quasi-fictional future demands due to the fact that they are created without real counterparts. The capacity of production systems in developed countries to respond to increases in money supply by creating more wealth, involves the assumption of money neutrality in the long-run. However, in developing countries, the excess of money supply may lead to inflation trends. The present study has confirmed the long-term non-neutrality of money supply in the USA, and its neutrality in Gabon and Morocco. Key words: Money neutrality, Developed countries, Developing countries, SVEC model. JEL: E41, E42, E51, E52.